Efektifitas Pemberian Suplemen Serbuk Kunyit (Currcuma longa L.) Terhadap Jumlah Bakal Telur (Hierarki Folikel) Puyuh Jepang (Coturnix-coturnix japonica L) - Sukarman Hadi Jaya Putra (Biota, 2017)
The purpose of this research was to study the effect of turmeric powder supplementation prior to sexual maturity of Japanese quail’s egg. Forty-five of female quils were assigned into completely randomized design with 3 treatments (P0: without tumeric powder or control, P1: level of turmeric powder 54 mg/quail/day, P2: level of turmeric powder 108 mg/quail/day) and each treatments used 3 quils with 5 replications respectively. The treatments were administrated every day for 30 days started at the age of 14 days. Parameters measured were number of follicles hierarchy. Statistical analysis used ANOVA followed by Duncan’s test. The result showed that administrated turmeric powder suplementation at level 108 mg/quail/day had significantly increase the number of Japanese quail follicles hierarchy prior to sexual maturity.